Evaluation of Transfer Pricing Methods in Related-Party Royalty Transactions for Trade Name at PT. ABC - Delfiana Primashinta Iskandar; Arifin Rosid (Universitas KH. Abdul Chalim Mojokerto, 2026)
Global economic growth increases cross-border transactions between affiliated entities. From tax perspective, this rise challenges in terms of evaluate the arm’s length prices of a transaction between related parties. This research aims to evaluate the transfer pricing methods in related-party transactions concerning royalty payments for the use of a trade name at PT. ABC. This case study use a qualitative approach through an examination of transfer pricing documentation, tax regulations, and interviews with the company’s internal representatives, an independent tax consultant, and tax auditors. The analysis employs comparability analysis in accordance with the OECD Transfer Pricing Guidelines (2022) as well as domestic regulations such as PMK-22/PMK.03/2020 and PMK-172/2023. Findings indicate evaluation of the most apporpriate method selection shows that, although the arm’s length price evaluation was conducted using the Comparable Uncontrolled Price (CUP) method by comparing the royalty rate with independent transactions under comparable conditions, the trade-name royalty is in substance more consistent with the characteristics of the Comparable Uncontrolled Transaction (CUT) method as defined in domestic regulations for transactions involving intangible assets.